Differentiation of pluripotent stem cells into cardyomyocytes is influenced by size of embryoid bodies - Budash, G.V.; Bilko, D.I.; Bilko, N.M. (Вiopolymers and Cell, 2016)
Aim. To find the relationship between the size of embryoid bodies and the efficiency of pluripotent stem cells differentiation into cardiomyocytes. Methods. Transgenic murine iPSC line AT25 and D3 ESC line αPIG (clone 44) were differentiated into cardiomyocytes in AggreWell plates containing microwells which cause the pluripotent stem cells to aggregate into EBs of an appropriate size. Both cell lines were genetically modified and expressed IRES-flanked enhanced green fluorescent protein (eGFP) under the control of cardiac alpha myosin heavy chain promoter. We applied flow cytometry and fluorescence microscopy to test the efficiency of the differentiation processes. Results. The efficiency of differentiation of embryoid bodies formed from iPSC line AT25 and containing 250 and 1000 cells was found to be lower as compared to embryoid bodies formed of 500 and 750 cells. The number of eGFP+ cells derived from embryoid bodies of 500 cells was 8.5 times higher compared to embryoid bodies of 250 cells (2.86 ± 0.30 % cardiomyocytes per embryoid bodies of 500 cells vs. only 0.34 % cardiomyocytes per embryoid bodies containing 250 cells); the difference was 4.7 times higher in comparison with embryoid bodies formed from 1000 cells. Conclusions. The size of embryoid bodies can affect differentiation of pluripotent stem cells into cardiomyocytes. Among the embryoid bodies formed from 250 to 2000 cells per embryoid body, the highest percentage of eGFP+ cells was obtained from 500-cell embryoid bodies.